2015
DOI: 10.1108/ijbm-02-2014-0031
|View full text |Cite
|
Sign up to set email alerts
|

The impact of internal brand management on employee job satisfaction, brand commitment and intention to stay

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 39 publications
4
75
0
3
Order By: Relevance
“…Job satisfaction refers to the pleasurable or positive emotional state resulting from the appraisal of one's job or job experiences (Bang, 2015). The organizational behavior literature is replete with both theoretical and empirical evidence that organizational commitment fully or partially mediates the relationship between job satisfaction and turnover intention (Preez and Bendixen, 2015). Turnover intention is defined as the intention of an organizational member, and if individuals are not satisfied with their jobs, they are less likely to stay with the organizations, which eventually causes a turnover (Bang, 2015).…”
Section: Intention To Staymentioning
confidence: 99%
“…Job satisfaction refers to the pleasurable or positive emotional state resulting from the appraisal of one's job or job experiences (Bang, 2015). The organizational behavior literature is replete with both theoretical and empirical evidence that organizational commitment fully or partially mediates the relationship between job satisfaction and turnover intention (Preez and Bendixen, 2015). Turnover intention is defined as the intention of an organizational member, and if individuals are not satisfied with their jobs, they are less likely to stay with the organizations, which eventually causes a turnover (Bang, 2015).…”
Section: Intention To Staymentioning
confidence: 99%
“…Job satisfaction is an important part of the HRM context. Numerous studies have confirmed the impact of a strong brand on employee satisfaction (Bergami and Bagozzi, 2000;Dukerich et al, 2002;Ellemers et al, 2002;Helm, 2013;Priyadarshi, 2011;Du Preez and Bendixen, 2015;Smidts et al, 2001) and the impact of job satisfaction on the employer brand (Brief and Weiss, 2002;Herrbach and Mignonac, 2004;Van Katwyck et al, 2000). However, customer perceptions of employees' levels of satisfaction and the impact on customers' willingness to buy or pay extra for the brand have not yet been studied.…”
Section: Hrm and Brandingmentioning
confidence: 99%
“…Locke and Latham (l990) also reported a positive correlation between satisfaction and commitment thus forming the basis on our next hypothesis. Du Preez and Bendixen (2015) found job satisfaction to have a dominant influence on brand commitment in the context of financial services sector. Further, Yi et al (2011) found a positive association of customer satisfaction with customer commitment using an electronic firm as the pre ferred sample.…”
Section: Customer Satisfaction and Customer Commitmentmentioning
confidence: 99%